GROWTH OF ULTRATHIN IRON FILMS ON CU(001) - AN ION-SCATTERING SPECTROSCOPY STUDY - Fauster, Thomas; et al. (Surface Science, 1993)
Low-energy ion scattering has been applied to study the pseudomorphic growth of ultrathin fcc iron films on a Cu(001) single-crystal surface. At all coverages - even as low as 0.1 monolayer (ML) - iron is found to about equal amounts in both the surface and the first subsurface layer, since pat of the iron atoms are incorporated into the original copper surface. This is particular evident for the 0.1 ML film, which does not exhibit any iron defects, such as steps or adatoms. Instead copper surface defects become visible upon iron deposition. Near 2 ML the substrate is covered for the most part by a relatively smooth bilayer indicating the coalescence of the iron islands. Up to a film thickness of around 6 ML the surface defect density of the iron layers decreases with increasing coverage and raises again at larger coverages. Above approximately 10 ML the pseudomorphic fcc growth breaks down and domains of bcc iron with (110) orientation are formed.